2017
DOI: 10.4038/sljch.v46i3.8320
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding manifestations in dengue and their correlation with the platelet count

Abstract: Objective: To study the common bleeding manifestations in dengue and see whether there is a correlation between them and platelet counts less than 100,000/cu.mm. Method:Children below the age of 14 years with dengue seropositivity were included in the study. Relevant blood investigations were done and patients were managed according to World Health Organisation guidelines. Results:A total of 100 children with a mean age of 7.9 ± 3.7 years were included in the study. During the course of illness, bleeding occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
3
6
1
Order By: Relevance
“…Sreenivas et al, found that 26% of cases had melaena, 20% had petechiae, 8% had haematemesis, 4% had epistaxis and 2% had gum bleeding. 25 Hematuria was the least common finding among our patients , accounting for about 1%, it was reported the same in the earlier studies of Sreenivasan et al, Narayanan et al, that bleeding by the urogenital tract is less common among the bleeding manifestations. 14,25 Various types of complications were seen during course of disease.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Sreenivas et al, found that 26% of cases had melaena, 20% had petechiae, 8% had haematemesis, 4% had epistaxis and 2% had gum bleeding. 25 Hematuria was the least common finding among our patients , accounting for about 1%, it was reported the same in the earlier studies of Sreenivasan et al, Narayanan et al, that bleeding by the urogenital tract is less common among the bleeding manifestations. 14,25 Various types of complications were seen during course of disease.…”
Section: Discussionsupporting
confidence: 83%
“…25 Hematuria was the least common finding among our patients , accounting for about 1%, it was reported the same in the earlier studies of Sreenivasan et al, Narayanan et al, that bleeding by the urogenital tract is less common among the bleeding manifestations. 14,25 Various types of complications were seen during course of disease. These were hepatopathy, acute renal failure (nephropathy), ascites, Pneumonia, dengue hemorrhagic fever(DHF), Dengue complicated with shock (DSS), multi-organ dysfunction syndrome and extended dengue syndrome.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thrombocytopenia is usually mild, asymptomatic but may be associated with bleeding 18 along with vasculopathy, coagulopathy and platelet dysfunction. 5 It may 13,17,19 or may not correlate with severity of bleeding 15,18 and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia is usually mild, asymptomatic but may be associated with bleeding 18 along with vasculopathy, coagulopathy and platelet dysfunction. 5 It may 13,17,19 or may not correlate with severity of bleeding 15,18 and complications. 10,15 Platelet counts drop between 3 rd -7 th days, normalise by 8th-10 th days reach a nadir between 4-7 th day 5,8,11,14 coinciding with late febrile and early critical preshock period which precedes the rise in hematocrit 2,6,15 .…”
Section: Discussionmentioning
confidence: 99%